Preparing Composite Materials Based on Unsaturated Polyester with Natural Materials of Plant Origin and Studying Some of Their Mechanical and Physical Properties - Ibrahim, Abdulraheem; Aleabi, Suad H.; Mahdi, Khalid H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The process of burning solid waste causes a serious environmental problem, leading to air and water pollution. Therefore, these agricultural wastes are added as reinforcing materials to polymers through which some mechanical and physical properties can be improved. This study included the preparation of single and hybrid polymeric composite materials from polyester resin as a base material. Powders of both sawdust and sunflower seeds were used as reinforcement materials with different weight fractions (5,10,15)%  and a granule size of 75µm. Some mechanical properties were studied, including bending strength testing, bending elastic modulus, impact strength, and surface hardness testing, in addition to thermal conductivity. The obtained results showed an amelioration in some mechanical characteristics in varying proportions for both the bending test and the bending elastic modulus. As for the impact test and surface hardness, there is an increase in their values ​​compared to their value for the pure polyester material. As for the thermal conductivity test, both single and hybrid composite materials exhibit decreased thermal conductivity values across different weight fractions.